From formulation to function: A detailed review of microbial biofilms and their polymer-based extracellular substances - Baljeet Singh Saharan; Nisha Beniwal; Joginder Singh Duhan (The Microbe)
Microbial biofilms are organized bacterial populations that stick to surfaces and are encased in an extracellular polymeric substances (EPS). Biofilms can form on both animate and inanimate surfaces and are acknowledged for their resilience against environmental stresses and antimicrobial agents. Extracellular polymeric substances (EPS) are responsible for establishing the structural and functional integrity of microbial biofilms. The primary constituents of EPS discharged into the environment by microorganisms consist of polysaccharides, proteins, lipids, and extracellular DNA (eDNA). Mature biofilms have viscoelastic properties as a result of the presence of exopolysaccharides and eDNA. This characteristic makes it difficult to detach the biofilm from the underlying surface, even under intense mechanical pressure or continuous fluid shear stress. Factors including species, substrate type, light intensity, temperature, pH, and nutrition availability might influence the composition of EPS. Several researchers have examined the structure and interrelationships of the EPS matrix derived from bacterial biofilms of A. baumannii, E. faecalis, Entercoccus. spp, P. aeruginosa, K. pneumoniae, and S. aureus. The most common carbohydrates are mannose, galactose, and glucose, with N-acetyl-glucosamine, galacturonic acid, arabinose, fucose, rhamnose, and xylose being present in large quantities. In addition to this, biofilms have several applications across various disciplines of biology. So, this review emphasize on the formation and function of bioflim.